Determinan Maternal Kejadian Preeklampsia: Studi Kasus di kabupaten Tegal, Jawa Tengah - Fatkhiyah, Natiqotul; Kodijah, Kodijah; Masturoh, Masturoh (Jurusan Keperawatan FIKES UNSOED, 2016)
Preeclampsia and Eclampsia are prolonged pregnancy complications, with typical symptoms such as hypertension, edema and proteinuria. The dominant factors related to the incidence of preeclampsia has not reveled yet, therefor appropriate prevention and intervention efforts are needed. Idenfitying risk factors of preeclampsia are expected to prevent and to control risk factors appropriately to decrease mothers and infants Ã‚Â morbidity and mortality Ã‚Â caused by preeclampsia. This research was to identify determinants of maternal factors (age, gravidity, history of hypertension and ANC (antenatal care) to the incidence of preeclampsia. The study was an observational study with case control design to analyze the relationship between determinant Tractors (age, gravidity, history of hypertension and ANC) and the preeclampsia. The case was pregnant and in labor women with preeclampsia, while The Control was mothers without peeclampsia since pregnancy to delivery. Following then, exposure determinant factors to incidence of preeclampsia was examined. The Renault showed that risk factors were associated with the incidence of preeclampsia included age, history of hypertension and a history of preeclampsia (p value <0.05). The history of hypertension was the riskiest factor by OR 6,42. It was expected that health professionals, especially midwives are capable to provide high quality antenatal care to guarantee early detection of obstetric complications.>